AB0525 Local open-label multicenter study to evaluate the quality of life in patients with moderate to severe active rheumatoid arthritis and an inadequate response to DMARDS when adding tocilizumab. (23rd January 2014) - Nasonov, E.; Panasyuk, E.; Shikina, E.; Plaksina, T.; Dmitrieva, A.; Troegubova, L.
Abstract : Background: Rheumatoid Arthtritis (RA) is systemic autoimmune disease affecting 1% of the population. The disease process is characterized by persistent synovitis and progressive joint destruction leading to disability. In spite of some biological therapies most of RA patients don't reach good quality of life. Objectives: Primary objective: to assess the change in rheumatoid arthritis (RA) quality of life with adding of tocilizumab (TCZ) to traditional DMARDs (tDMARDs) therapy Secondary objective: to assess the efficacy of TCZ in combination with tDMARDs in terms of the change in DAS28, ACR 20/50/70 responses and EULAR response at Week 24 and safety based on the reports on adverse events, serious adverse events, laboratory data and vital signs Methods: A multicentre open-label phase IV study was performed from August 2009 till February 2011. A total 202 adult patients with active RA (DAS>3, 2) who had not been treated previously with any biological agents were enrolled in the study. Patients remained on stable doses of tDMARDs and recieved TCZ 8 mg/kg every 4 weeks for 24 weeks (total 6 infusions). Mean age of the patients was 49±12 years. And their mean disease duration was 7, 5±6, 5 years. Results: Average disease activity score (DAS) 28 of all 202 patients significantly decreased from 6, 75±0, 85 (baseline) to 2, 6±1, 18 (week 24). DAS28 remission (DAS28<2, 6) rate at week 24 being achieved by 51, 3%, SDAI remission – 21, 4%. ACR 20/50/70 responses were achieved by 88, 6/70, 3/44, 1% patients at week 24. Response was seen early - 50% patients had ACR20 improvement at week 4. 38, 3% was established by ACR70 at week 24. C-reactive protein levels was reduced from 33, 5±34, 84 (baseline) to 4, 78±12, 94 (week 24). 88% patients had a clinically meaningful improvement in physical function measured by Health Questionnaire Disease Index (HAQ-DI). The safety profile of TCZ was comparable to that previously observed in the phase III trial programme. There were registered 100 AEs in 51 (25, 2%) patients. Most of AE were mild or moderate. Which were mostly high level transaminases (29%) and respiratory infections (17%). 73% of AEs resolved by the time of reporting. There were 14 serious AEs. Conclusions: Tocilizumab in combination with traditional DMARDs is highly effective in the treatment of moderate to severe RA with a rapid and sustained improvement in signs and symptoms. Rapid and sustained improvement was also noted in quality of life. A manageable safety profile was seen over the 24-week study period. Disclosure of Interest: None Declared